Effects of H₂SO₄, HCl, and MgSO₄ Attack on Porcelain-Based Geopolymer Concrete - Klingsad, Rada; Israngkura Na Ayudhya, Borvorn (Civil Engineering Journal, 2025)
This study examined the durability of porcelain-based geopolymer concrete when exposed to strong acids, chlorides, and sulfates. Specimens prepared with a 14M NaOH solution and initially cured at 105°C for 24 hours were submerged in acidic and alkaline solutions for varying durations—3, 7, 14, 21, 28, 60, and 90 days. Compressive and splitting tensile strength tests were conducted to assess material performance. The results showed that immersion in H₂SO₄, HCl, and MgSO₄ solutions led to weight loss and reductions in both compressive and splitting tensile strengths. Strength deterioration was more pronounced in the early stages, with a peak weight loss rate of 15.32 g/day. After 90 days in 20% H₂SO₄, 20% HCl, and 20% MgSO₄ solutions, the residual compressive strengths were measured at 2.80, 14.19, and 3.29 N/mm², respectively, while splitting tensile strengths were recorded at 0.40, 1.21, and 0.51 N/mm². The ratio of splitting tensile strength to compressive strength (fsp/f’c) was influenced by molar concentration and immersion duration. Experimental findings revealed that a high molarity NaOH solution and elevated curing temperature enhanced resistance to HCl attack more effectively than H₂SO₄ and MgSO₄. Moreover, the experimental data closely aligned with the ACI 318 design code, though it tended to overestimate tensile strength.